Waste Reduction In Healthcare Department By Implementing Value Stream Mapping Technique - Hasbullah, Nor Wahida (2016)
Although lean manufacturing has been employed in different sectors, its usage is more prominent in the manufacturing area. However, now the trend is certainly also spreading to other domains like the hotel and the healthcare sectors. In the healthcare domain, this approach is typically called lean healthcare. For several years, patient waiting time has remained a grave concern. Initially, it might look like the patient is not perturbed about waiting for a treatment. However, it was clear from a survey conducted in the service sector that the waiting experience is typically disapproving and has evidently impacted the overall contentment of customers with the service being offered. In Malaysia, the overall waiting time for patients in different clinics ranges from 18 to 85 minutes. Around 21 percent of patients seem to be discontented; in other words, their experienced was unfair. This study, carried out in Polyclinic Ayer Keroh, Melaka, involves workers and patients connected to the healthcare system. A robust lean tool called Value Stream Mapping is formulated to ascertain the waste existing in the present process of the healthcare system. According to the results, there is an unnecessary waste existing, including personal attitude, ambiguous information, and outmoded patient approach and clinic layout, which cause prolonged waiting times. Recommendations are made for the deployment of a new user interface, Kanban, 5s, and re-design of the present mechanism for healthcare organisations, which offer greater value-added time for patients as well as the staff, thereby decreasing the non-value added time and the waiting time.